The Maxilla-Mandibular Discrepancies through Soft-Tissue References: Reliability and Validation of the Anteroposterior Measurement - Cinzia Maspero; Niccolò Cenzato; Francesco Inchingolo; Maria Grazia Cagetti; Gaetano Isola; Davide Sozzi; Massimo Del Fabbro; Gianluca Martino Tartaglia (Children, 2023)
This research aimed to identify a new measurement to diagnose the sagittal maxillary and mandibular difference that considers the patient’s profile (soft tissue Wits appraisal: obtained by projecting points A and B on the occlusal plane and subsequently measuring the linear distance between the two points). This new measurement was compared to the conventional Wits appraisal obtained to diagnose sagittal jaw discrepancy. In total, 300 subjects (162 males, 138 females) aged between 6 and 50 years requiring orthodontic treatment were analyzed. The cephalometric tracings on the pre-treatment lateral cephalometric radiographs were obtained and the two measurements taken were the Wits appraisal and a new measurement which were both calculated and compared. The analysis of the linear correlations between the conventional Wits value and the measurement obtained on the soft-tissue were undertaken. The relevance was established at 5% (p < 0.05). The mean values were also calculated within sex and age classes, and comparisons between sexes were obtained employing the t test Student’s for independent samples. Subsequently, chi-square analysis was also utilized to verify the sex distributions in the age groups considered. The results obtained suggested that these two measurements were significantly correlated with each other, with no characteristic patterns of sex or age. These data allowed an estimation of the reference values of the new measurement (−1.9 mm and 5.4 mm for patients with Class I molar relationship) showing that the former was more variable than the latter. The new measurement could allow for an accurate evaluation of the jaws sagittal discrepancy from soft tissue analysis.